On Some Lacunary Generalized Difference Sequence Spaces of Invariant Means Defined by a Sequence of Modulus Functions - Atici, Gulcan; Bektas, Cigdem Asma (Kyungpook Natl Univ, Dept Mathematics, 2011)
The aim of this paper is to introduce and study the sequence spaces [w, theta, F, p, q] infinity [w, theta, F, p, q]1(Delta(m)(v)) and [w, theta, F, p, q](0)(Delta(m)(v)), which arise from the notions of generalized difference sequence space, lacunary convergence, invariant mean and a sequence of Moduli F = (f(k)). We establish some inclusion relations between these spaces under some conditions.
Keywords: Invariant mean; Difference sequence spaces; lacunary sequence; modulus function